2020
DOI: 10.1038/s41593-020-00758-5
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory transmucosal SARS-CoV-2 invasion as a port of central nervous system entry in individuals with COVID-19

Abstract: here is increasing evidence that SARS-CoV-2 not only affects the respiratory tract but also impacts the CNS, resulting in neurological symptoms such as loss of smell and taste, headache , fatigue, nausea and vomiting in more than one-third of individuals with COVID-19 (refs. 1,2). Moreover, acute cerebrovascular disease and impaired consciousness have been reported 3. While Olfactory transmucosal SARS-CoV-2 invasion as a port of central nervous system entry in individuals with COVID-19

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

42
1,276
7
26

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 1,153 publications
(1,459 citation statements)
references
References 51 publications
42
1,276
7
26
Order By: Relevance
“…We showed evidence of SARS-CoV-2 RNA using qRT-PCR in a FFPT myocardial tissue although the exact anatomical location of viral RNA evidence could not be proven with ISH methodology, implying an indirect endothelial damage possibly triggered and enhanced by the inflammatory cellular reaction rather than the virus itself. On the other hand, IF labelled reaction products similar as recently described in central nervous vascular endothelium using the same methodology with qRT-PCR and IF labeling on FFPE autopsy tissue as in our cohort, further support a direct endothelial damage though the SARS-CoV-2 virus [ 60 , 64 ].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…We showed evidence of SARS-CoV-2 RNA using qRT-PCR in a FFPT myocardial tissue although the exact anatomical location of viral RNA evidence could not be proven with ISH methodology, implying an indirect endothelial damage possibly triggered and enhanced by the inflammatory cellular reaction rather than the virus itself. On the other hand, IF labelled reaction products similar as recently described in central nervous vascular endothelium using the same methodology with qRT-PCR and IF labeling on FFPE autopsy tissue as in our cohort, further support a direct endothelial damage though the SARS-CoV-2 virus [ 60 , 64 ].…”
Section: Discussionsupporting
confidence: 86%
“…Direct endothelial viral damage has been documented in several previous studies using in vivo or in vitro samples [ 59 , 60 ]. Vascular organoids infected with SARS-CoV-2 were described earlier this year and the recently published study by Meinhardt et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A genomewide association study identified a kidney failure-related 3p21.31 gene cluster as a genetic susceptibility locus in patients with COVID-19 with respiratory 36 . Moreover, a latest study demonstrated the presence of SARS-CoV-2 RNA and protein in anatomically distinct regions of the nasopharynx and brain 37 . Cumulative evidence indicate that a heart-brain-kidney network 38 may be associated with SARS-CoV-2 infection.…”
Section: /14mentioning
confidence: 99%